2020
DOI: 10.1177/0003489420938100
|View full text |Cite
|
Sign up to set email alerts
|

KTP Laser Treatment of Early Glottic Cancer: A Multi-Institutional Retrospective Study

Abstract: Objectives: The primary objectives were to report oncologic outcomes of transoral laser microsurgery with potassium-titanyl-phosphate (KTP) laser (TLM-KTP) ablation of early glottic cancer (EGC). The secondary objectives were to report vocal outcomes and to analyze factors that might influence outcomes. Methods: A multi-institutional, retrospective analysis of consecutive patients treated for T1 or T2 glot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…32 Similarly, Parker et al reported a very low recurrence rate of 2% following KTP. 28 These findings indicate that KTP is associated with a similar recurrence rate to radiotherapy and CO 2 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…32 Similarly, Parker et al reported a very low recurrence rate of 2% following KTP. 28 These findings indicate that KTP is associated with a similar recurrence rate to radiotherapy and CO 2 .…”
Section: Discussionmentioning
confidence: 66%
“…The final meta-analysis included eight studies (Figure 1). 6,[27][28][29][30][31][32][33] A total of 342 patients underwent KTP laser ablation within the included studies. All the included studies were performed between 2013 and 2022.…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
“…In addition to the use of CO2 gas laser, solid-state diode lasers have also been investigated for their potential use in transoral surgery. 11,[13][14][15][16][17] The limitations of CO2 laser, namely field of view constraints, narrow penetration, and cost, prompted the investigation of using other lasers like KTP (potassium titanyl phosphate) and dual-wavelength optic fiber laser. Compared to CO2 laser, KTP laser has been found to have superior coagulative capability and greater penetration.…”
Section: Energy Devices For Tlm and Torsmentioning
confidence: 99%
“…Laser ablation in glottic cancers with ultranarrow margins has been shown to be effective in preserving vocal function without the need for further adjuvant radiotherapy ( 5 ). This can be used even for bulky tumors that are early stage, with the advantage of minimal thermal spread to the surrounding normal tissue ( 6 ). Now, with the human papilloma virus–associated oropharyngeal cancer epidemic that is associated with improved outcomes and where narrower margins for resections are needed, the use of laser for resections has been shown to improve pain scores and to reduce hospital stay and time to oral feeding when compared with the use of traditional cautery ( 7 ).…”
Section: Introductionmentioning
confidence: 99%